Contributions of Natural and Anthropogenic Forcing Agents to the Early 20th Century Warming - Egorova, Tatiana; Rozanov, Eugene; Arsenovic, Pavle; Peter, Thomas; Schmutz, Werner (Frontiers in Earth Science, 2018)
The observed early 20th century warming (1910 – 1940) is one of the most intriguing and less understood climate anomalies in the twentieth century. To investigate the contributions of natural and anthropogenic factors to the surface temperature changes, we performed seven model experiments using the chemistry-climate model with interactive ocean SOCOL3-MPIOM. Contributions of energetic particle precipitation, heavily (shortwave UV) and weakly (longwave UV, visible and infrared) absorbed solar irradiances, well-mixed greenhouse gases, tropospheric ozone precursors and volcanic eruptions were considered separately. Model results suggest only about 0.3 K of global and annual mean warming during the considered 1910-1940 period which is by about 25% smaller than the trend obtained from observations. We found that the half of the simulated global warming is caused by the well-mixed greenhouse gases (WMGHG: CO2, CH4 and N2O) increase, while the increase of the weakly absorbed solar irradiance is responsible for approximately one third of the total warming. Because the WMGHG behavior is well constrained only higher solar forcing or including new forcing mechanisms can help to reach better agreement with observations. The other considered forcing agents (heavily absorbed UV, energetic particles, volcanic eruptions and tropospheric ozone precursors) contribute less than 20% to the annual and global mean warming, however they can be important on regional/seasonal scales.